Rural entrepreneurship: leveraging social media for circular economies and green activism - Christofi, Michael; Zahoor, Nadia; Khalid, Adeel; Usman, Muhammad (Springer Science+Business Media, 2026)
This study builds on the dynamic capability view to propose that rural entrepreneurs’ social media use is positively related to circular economy practices and green activism. Drawing on time-lagged data from 307 rural entrepreneurs, the results reveal significant positive associations, with green knowledge acquisition mediating these relationships. Furthermore, entrepreneurs’ political skill moderates the effect of social media use on green knowledge acquisition, strengthening its role in enabling sustainable outcomes. These findings highlight the potential of social media to drive environmentally responsible practices and advocacy in rural communities. By enabling rural entrepreneurs to adopt circular economy practices and engage in green activism, social media fosters environmental conservation and empowers individuals’ participation in sustainability efforts. This study contributes to research on rural entrepreneurship, social media use, and sustainability by identifying key mechanisms and boundary conditions, while offering practical implications for supporting environmentally responsible innovation in resource-constrained rural economies.
Keywords: Rural entrepreneurs; Social media use; Political skill; Green knowledge acquisition; Green activism; Circular economy practices; Rural communities; Resource-constrained settings; fi=InnoLab|en=InnoLab|